2014
DOI: 10.1177/0003489414550241
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 2 Methods of Endoscopic Laryngeal Sensory Testing

Abstract: Sensory impairment detected by the air pulse method does not appear to be associated with risk of penetration/aspiration. Significant laryngeal sensory loss revealed by the touch method is associated with compromised airway protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…In another study with patients after radiotherapy of head and neck tumors, this association could not be confirmed . One explanation for the discrepant findings may be a low inter‐observer agreement, which is likely due to the difficulty in establishing a standard distance to the pharynx from the tip of the endoscope . In our study, we tried to avoid a similar problem by using quantifiable liquid volumes.…”
Section: Discussionmentioning
confidence: 75%
“…In another study with patients after radiotherapy of head and neck tumors, this association could not be confirmed . One explanation for the discrepant findings may be a low inter‐observer agreement, which is likely due to the difficulty in establishing a standard distance to the pharynx from the tip of the endoscope . In our study, we tried to avoid a similar problem by using quantifiable liquid volumes.…”
Section: Discussionmentioning
confidence: 75%
“…FEESST involves observation of an objective marker of laryngeal sensation by eliciting the laryngeal adductor reflex (LAR), or a brief protective closure of the vocal cords, by delivering air pulses to the mucosa . Langmore has compared this method to eliciting the LAR by touching the arytenoids with the laryngoscope . While laryngeal sensory testing has been shown to be safe and potentially equal to MBS in anticipating pneumonia, it has not yet been broadly adopted .…”
Section: Discussionmentioning
confidence: 99%
“…This sequential motor activity of muscles is modulated by sensory feedback and sensory input plays essential part in pharyngeal swallow . It has been demonstrated that the application of sensory stimulation in oropharyngeal area modulates swallowing performance and involves facilitation of swallowing initiation Sensory impairments in pharyngeal area are associated with penetration or aspiration in dysphagic patients, and oropharyngeal anesthesia results in disruption of swallowing movement even in healthy humans . Furthermore, impaired pharyngeal sensitivity is associated with reduced cortical activation …”
Section: Introductionmentioning
confidence: 99%